Pesticide Effect on Populations of Tetranychus urticae Koch (Acari: Tetranychidae) and a Predaceous Mite on Table Grapes in the Hex River Valley - Schwartz, A. (South African Journal of Enology and Viticulture, 2017)
Tetranychus urticae Koch is a pest of different table grape cultivars in the Hex River Valley. Two seasonal colour forms of this mite occur. The spring and summer form is straw-coloured to light green (green form), whereas the late summer females are light red to brick-coloured (carmine form). The green form was more abundant on young leaves on which feeding caused a yellow stippling. These leaves dried out and turned brown, and young shoots became stunted. This form also caused chlorosis on mature leaves. It occurred in maximum numbers in October. The carmine form caused bronzing or chlorosis of mature leaves, with infestation peaks in February or March. The results suggested that T. urticae infestations were caused by broad-spectrum insecticides, viz. organo-phosphates and synthetic pyrethroids, which were applied for the control of key pests. This was largely brought about by the destruction of the predaceous mite, Amblyseius addoensis Van der Merwe & Ryke, an important predator of T. urticae.